Effect of micromineral and phenylpropionic acid on performances of coccus and rod-shaped cellulolytic bacteria degrading fibre of forage - Thalib, Amlius; Haryanto, B; Kompiang, S; Mathius, I-W; Aini, A (Indonesian Animal Sciences Society, 2000)
Performances of coccus and rod-shaped cellulolytic bacteria as inoculum for fermentation of fibrous substrate treated with growth or stimulator factors have been conducted by in vitro. The bacteria were firstly separated and purified based on their morphological shape and followed by identification of their gram type. The treatments as follow : control, Cu (1,0 ppm), Zn (6,0 ppm), Se (0,02 ppm), Fe (16 ppm), Co (0,02 ppm), Mn (4,0 ppm), Mo (0,002 ppm), and phenylpropionic acid (PPA) (30 ppm). These factors were added into fermentation media individually (F.P/S) and as mixture (Mix F.P/S). Substrates used were cellulose and rice straw. Measurements were bacterial digestion of drymatter (DMD), bacterial count, volatile fatty acids (VFA) and NH3-N contents. Gram test showed that inoculum cellulolytic cocci and rods are gram-positive and gram-negative consecutively. The results of treatments showed that Cu, Zn, Co, Mo and PPA improve digestibility of cellulose and rice straw substrates by cellulolytic cocci significantly (p<0.05), and beside Mn, these factors increased the total count of cellulolytic cocci in fermentation medium significantly (p<0.05). The growth or stimulator factors increasing digestibility values of the substrates by cellulolytic rods significantly (p<0.05) were Cu, Zn, Se, Fe, Co, Mn and Mo (except Mn for rice straw substrate). Only 4 elements of the growth and stimulator factors increasing the total count of cellulolytic rods during fermentation of cellulose and rice straw substrates significantly (p<0.05) that is Zn, Co, Mn and Mo. Digestibility of cellulose by cocci is higher than by rods (34.65% vs 29.87%), however, the digestibility of rice straw by both bacteria did not show difference. Digestibility of both cellulose and rice straw substrates was improved by cocci and rods combination and improved further when treated with Mix F.P/S. Parameters of fermentation media ecosystem measured (i.e. total count of bacteria, VFA and NH3-N) were generally changed to be better when treated with Mix F.P/S. It is concluded that performances of cocci and rods in digesting fibrousÂ substrate are different, and growth or stimulator factors improved the activities of both group of bacteria significantly. Â Key words : Cellulolytic cocci, cellulolytic rods, growth and stimulator factors, bacterial digestion